Stress Factors, Stress Levels, and Coping Mechanisms among University Students - Abdullah Alkhawaldeh; Omar Al Omari; Samir Al Aldawi; Iman Al Hashmi; Cherry Ann Ballad; Amal Ibrahim; Sulaiman Al Sabei; Arwa Alsaraireh; Mohammad Al Qadire; Mohammed ALBashtawy (The Scientific World Journal)
Aims. To explore university students’ levels of stress, stressors, and their coping style. Methods. A cross-sectional correlational design with a convenience sample (n = 676) of university students who completed the Student-Life Stress Inventory (SSI) and Coping Strategies Indicator (CSI) was used. Findings. Overall, two-thirds of the participant reported moderate levels of stress. Students with chronic illness, living alone, low CGPA, and having exams today experienced a statistically higher mean level of stress. Students who are living alone used the “avoidance” method more significantly and the “social support” method significantly less compared with students who are living with their families and friends. Conclusion. This study concurs with others that university students are prone to distress. To our knowledge, this is the first study in the region to explore the students’ coping skills. Some of the employed coping and associated factors could be used to lay the groundwork for evidence-based prevention and mitigation.